Data science for effective healthcare systems - Singh, Hari, 1957- (Boca Raton : Chapman & Hall/CRC Press, 2023)
"Data Science for Effective Healthcare Systems has a prime focus on the importance of data science in the healthcare domain. Various applications of data science in the health care domain have been studied to find possible solutions. In this period of COVID-19 pandemic data science and allied areas plays a vital role to deal with various aspect of health care. Image processing, detection & prevention from COVID-19 virus, drug discovery, early prediction, and prevention of diseases are some thrust areas where data science has proven to be indispensable. The aim of this book is also to provide the future scope of these technologies in the health care domain. Last but not the least, this book will surely benefit research scholar, persons associated with healthcare, faculty, research organizations, and students to get insights into these emerging technologies in the healthcare domain"--
OCLC-licensed vendor bibliographic record.
Keywords: Medicine -- Data processing; Medical informatics; Medicine -- Information technology; COMPUTERS / Database Management / Data Mining